Faktor Penentu Ekspor Komoditi Kayu Manis Indonesia - Indelman Indelman; Fery Andrianus; Neng Kamarni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
This study aims to analyze the determinants of Indonesian cinnamon exports to ten main destination countries. The analysis period used in this study is from 2000 to 2019 which uses the Gravity Model analysis with a panel data regression approach. The results of this study indicate that a good model in analyzing the determinants of Indonesian cinnamon exports is the Random Effect Model (REM). Based on the estimation results, the GDP of the destination country, Indonesia's real GDP, economic distance and the real effective exchange rate are factors that determine the volume of Indonesian cinnamon exports to the ten main export destination countries, while population and prices do not affect the volume of Indonesian cinnamon exports.